1998
DOI: 10.1089/end.1998.12.183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retropulsion Caused by Holmium: YAG Laser with Various Power Settings and Fibers

Abstract: The ideal intracorporeal lithotriper would comminute all types of calculi into small readily excreted particles. It would be small and flexible with an energy source safe for the uroepithelium. It should not break, should be inexpensive, and should not retropulse the stone up the urinary tract. This investigation was designed to quantify the last quality for the holmium:YAG laser. The mechanism of action of the pulsed Ho:YAG laser (wavelength 2100 nm) is the generation of a gas plasma at the stone-fluid interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…13,14 Furthermore, recent Ho:YAG laser lithotripsy retropulsion studies have concluded that the use of lower pulse energies, longer pulse durations, higher pulse rates, and smaller optical fiber diameters is the optimal combination of laser parameters for minimizing stone retropulsion. [15][16][17][18][19][20] A comprehensive study of all of these parameters was beyond the scope of this paper. However, it should be emphasized that, unlike the flashlamppumped Ho:YAG laser, the diode-pumped TFL is an ideal laser for operation within the range of laser parameters listed above, due to the TFL's excellent spatial beam profile that allows use of small-core fiber diameters and its operation at arbitrary pulse durations and pulse rates.…”
Section: Retropulsion Studiesmentioning
confidence: 99%
“…In urological applications, retropulsion is a common but an undesirable side effect of urological lithotripsy [11][12][13]. Investigations were carried out at the mechanism and its parameter dependency [14][15][16].…”
Section: This Issue Of Photonics and Lasers Inmentioning
confidence: 99%